Des généraux contre la transition démocratique. Armée, anticommunisme et déstabilisation de la démocratie en Espagne (1975-1982) - Matthieu Trouvé (Les Cahiers de Framespa)
The Spanish democratic transition (1975-1982) was marked by the strong anticommunism of several conservative pro-Franco military groups. This anticommunism was visible in four areas: their hostility to the political reforms carried out by the Suárez government; their strong opposition to the legalization of trade-unions and the PCE; the politicization of a few generals who had close ties to the extreme right-wing; and finally, the involvement of several officers in acts of political violence and coup attempts. The anticommunism of parts of the Spanish armed forces—which resulted from an overestimated fear of seeing the PCE return to power—can be understood as a way to justify their resisting the process of democratization. It was also based on a discourse stressing the return of the 1930s and the need to resort to military interventionism. But concluding that all the armed forces share the orientations of the Spanish extreme right would be excessive.